An Unusual Presentation of Oral Mucocele in Infant and Its Review. (26th August 2014) - Bhargava, Neha; Agarwal, Prateek; Sharma, Nitin; Agrawal, Mayank; Sidiq, Mohsin; Narain, Pooja
Abstract : Mucocele is a benign lesion characterized by an extravasation or retention of mucous in submucosal tissue from minor salivary glands. Mucoceles are known to occur most commonly on the lower lip, followed by the floor of mouth and buccal mucosa being the next most frequent sites. Trauma and lip biting habits are the main cause for these types of lesions. Mucocele is a common oral mucosal lesion but it is rarely observed in the infant. This paper highlights the successful management of a rare case of mucocele in an 11-month-old child. Diagnosis and management of mucocele are challenging. For this reason we felt it would be interesting to review the clinical characteristics, histological features, differential diagnosis, and their treatment and evolution in order to aid decision-making in daily clinical practice.